Playing-Side Analytics in Team Sports: Multiple Directions, Opportunities, and Challenges - Foster, George; O'Reilly, Norm; Naidu, Zachary (Frontiers in Sports and Active Living, 2021)
Abstract This paper describes developments in the player-side analytics in major team sports. We take a decision-making lens to the role of analytics in player decisions by general managers and coaches. We outline key accelerators and inhibitors to the wider adoption and acceptance of data analytics playing a greater role in the decisions of clubs. Contribution to the Field Statement This paper contributes to the existing research on data analytics and informs future practice on the topic. In terms of research contributions, the analysis of the 1998 to 2010 and 2010 to 2019 periods in Major League Baseball, informed by previous work in sabermetrics and a MLB case study, articulates trends in analytics in professional sport, provides evidence of its ability to support efficient use of salary budgets, and provides direction for future research on the topic. From a practical perspective, a series of accelerators and inhibitors, as well as specific directions, to leagues, clubs and agencies are provided that, if implemented, can enhance the adoption, use and acceptance of data analytics as an input into the player-side decisions of clubs in the major team sports. Acknowledgement The authors note the research assistance of Gerzain Gutierrez and Carlos Shimizu, and gratefully acknowledge the research support from the Kissick Family Foundation. The insightful and constructive comments of two reviewers provided valuable guidance for this paper. We are much appreciative of Kirk Goldsberry for giving permission to reproduce material from his Sprawball book, an important contribution to the sport analytics literature.